Reconciling the Rawlsian and the utilitarian approaches to the maximization of social welfare - Oded Stark; Marcin Jakubek; Fryderyk Falniowski (University of Tübingen, Faculty of Economics and Social Sciences, 2013)
Under a deadweight loss of tax and transfer, there is tension between the optimal policy choices of a Rawlsian social planner and a utilitarian social planner. However, when with a weight greater than a certain critical value the individuals' utility functions incorporate distaste for low relative income, a utilitarian will select exactly the same income distribution as a Rawlsian.
urn:nbn:de:bsz:21-opus-71641
Keywords: D31; D60; H21; I38; 330; Maximization of social welfare; Rawlsian social welfare function; Utilitarian social welfare function; Deadweight loss; Distaste for low relative income